Relational Capital and The Results of An Enterprise's Innovative Activity: The Case of IT Enterprises in Lubusz Voivodeship, Poland - Monika INKÓW (Communications of International Proceedings, 2023)
The aim of this article is to present the relationship between the external and internal relational capital of an enterprise and the results of its innovative activity. The first part of the paper discuss the essence of relational capital in the context of organizational innovativeness. The next part  present the results of the study.  The study is of a empirical type. During the study, the author used the ordinary interview method using a standardized interview questionnaire. In the second stage, the study was supplemented with a survey interview. The study involved 70 entities that were represented during interviews by owners or high-level management staff. The findings of the study confirm that the surveyed companies from the IT industry that conducted innovative activities have external and internal relational capital at an appropriate hight level. Appropriately shaped external relational capital can have a positive impact on the innovative activities of enterprises. The situation is completely different in the case of internal relational capital, where the results obtained in the case of Spearman's rank correlation index are downright surprising. The positive Spearman's rank correlation coefficient occurs here only between internal relational capital and the success of innovative activities, the remaining indicators have negative values.
Keywords: innovations; relational capital; IT industry